Needs Analysis of English for Medical Purposes: A Student Perspective - Rinawati, Rinawati; Trisnadi, Setyo; Murwantono, Didik (Language Circle: Journal of Language and Literature, 2022)
English has been integrated into medical curriculum in higher education in countries where English is not the official language of instruction. For medical students—non-English department students—English has been taught to meet specified academic and professional needs of learners in so-called English for specific purposes (ESP). To ensure that English program is relevant to the learner’s needs, a need analysis is required. This study aimed to investigate the English needs of the first-year medical students taking a compulsory program of English for academic purposes at Faculty of Medicine, Sultan Agung Islamic University. The data were collected using a questionnaire to assess the medical students’ purpose of learning English, the importance of learning English, language learning needs of major language skills (reading, writing, listening, speaking) and their preference of assessment type. The data were descriptively analyzed. Forty-five students consisting of 67 % female and 33% male completed the questionnaire. Most students (76%) used English when studying. All students agreed on the importance of English. The most important sub skill included reading technical article in medicine, listening to audio and listening oral presentation, giving spoken presentation, writing medical prescription. Individual achievement was the most preferred type of assessment. The medical students agreed on the importance of English specific purposes. The interpretation of findings will be useful for the design of English for specific purposes in the study setting.